1996
DOI: 10.1097/00007632-199610150-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Low Back Pain in Adolescents

Abstract: Back pain in adolescents is common; it increases with age and is recurrent, but in general does not deteriorate with time. Much of the symptomatology may be considered a normal life experience, probably unrelated to adult disabling trouble.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
274
5
24

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(328 citation statements)
references
References 20 publications
25
274
5
24
Order By: Relevance
“…In the current study, boys reported experiencing more LBP than did girls. These results, although reported by others [8,29], are not in accordance with the majority of previous studies, which document a higher prevalence of subjectively experienced LBP among females [3,18]. Differences in case-definitions used might be a possible explanation for such inconsistency, but also subtle differences in age and nature of the study samples.…”
Section: Discussioncontrasting
confidence: 87%
“…In the current study, boys reported experiencing more LBP than did girls. These results, although reported by others [8,29], are not in accordance with the majority of previous studies, which document a higher prevalence of subjectively experienced LBP among females [3,18]. Differences in case-definitions used might be a possible explanation for such inconsistency, but also subtle differences in age and nature of the study samples.…”
Section: Discussioncontrasting
confidence: 87%
“…The study findings indicated that the intervention resulted in increased back posture knowledge, improved postural behavior during material handling and while sitting during lesson time. Additionally, the intervention did not result in increased fear avoidance beliefs or augmented back pain prevalence, which may be a negative consequence of attention for back-related topics [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords Adolescents Á Low-back pain Á Physical activity Á Prevention Á Health promotion Background Low-back pain (LBP) is frequent among schoolchildren [1][2][3][4][5][6][7][8]. The occurrence increases with age, especially in the early teen-years [1, 2, 9, 10] so that, by age 14-17, 11-71% will have experienced at least one episode of LBP [1][2][3][4][5][9][10][11].…”
mentioning
confidence: 99%
“…The occurrence increases with age, especially in the early teen-years [1, 2, 9, 10] so that, by age 14-17, 11-71% will have experienced at least one episode of LBP [1][2][3][4][5][9][10][11]. Recurrent LBP during childhood seems to occur among 5-19% of all children [4,5,9], and LBP in childhood may be a forerunner of LPB in adult life [12].…”
mentioning
confidence: 99%